2007
DOI: 10.1161/01.hyp.0000250984.14992.64
|View full text |Cite
|
Sign up to set email alerts
|

Heightened Functional Neural Activation to Psychological Stress Covaries With Exaggerated Blood Pressure Reactivity

Abstract: Abstract-Individuals who show exaggerated blood pressure reactions to psychological stressors are at increased risk for hypertension, atherosclerosis, and stroke. We tested whether individuals who show exaggerated stressor-induced blood pressure reactivity also show heightened stressor-induced neural activation in brain areas involved in controlling the cardiovascular system. In a functional MRI study, 46 postmenopausal women (mean age: 68.04; SD: 1.35 years) performed a standardized Stroop color-word interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 38 publications
4
85
0
7
Order By: Relevance
“…This stressor‐battery controls for individual differences in task engagement and motor responding through performance titration procedures. We have also found, in previous work, that cardiovascular and behavioral responding to tasks of this battery is reliable across neuroimaging and laboratory‐based testing contexts 31. Accordingly, it may be appropriate for developing stress reactivity norms across a variety of populations.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This stressor‐battery controls for individual differences in task engagement and motor responding through performance titration procedures. We have also found, in previous work, that cardiovascular and behavioral responding to tasks of this battery is reliable across neuroimaging and laboratory‐based testing contexts 31. Accordingly, it may be appropriate for developing stress reactivity norms across a variety of populations.…”
Section: Discussionmentioning
confidence: 53%
“…To compute prestressor BP and HR, the final 3 measurements from the prestressor period were averaged. The incongruent condition—minus—resting BP/HR change scores (ΔBP, ΔHR) were used to compute cardiovascular reactivity to match our previous work 31, 32. These change (reactivity) scores averaged over the Stroop and MSIT tasks were used in analyses given the high correlations between task reactivity scores (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Critchley, Gianaros, and their colleagues have been especially active in this area [36][37][38][39][40]. Using positron emission tomography (PET), Critchley et al observed in six participants that regional cerebral blood flow (rCBF) in the right dorsal ACC (Brodmann's areas 32 and 24) and right posterior insular cortex covaried directly with mean arterial pressure (MAP) during physical and mental challenge [36].…”
Section: Blood Pressurementioning
confidence: 99%
“…In this study, positive covariation with MAP was also exhibited by activations in dorsolateral prefrontal cortex (PFC); supplementary motor area; and sections of temporal, parietal, and occipital cortices. In a follow-up study of 46 postmenopausal women, Gianaros et al demonstrated that, across individuals, those participants with larger blood pressure responses exhibited larger BOLD activations in left pregenual ACC (in this case, anterior portions of Brodmann's area 32, excluding area 24), left insula, and right posterior cingulate cortex (Brodmann's area 31) [38].…”
Section: Blood Pressurementioning
confidence: 99%
“…Gao et al found that the lateral cerebellar output (dentate) nucleus is not activated by the control of movement per se, but is strongly engaged during passive and active sensory tasks (Gao et al, 1996). Recent research of the cerebellum's contribution to cognitive processing and emotional processing have increased enormously, showing that the cerebellum is responsible for sensory perception, learning, memory, attention, linguistic, emotional control and conflict resolution processing (Mandolesi et al, 2001;Bischoff-Grethe et al, 2002;Vokaer et al, 2002;Claeys et al, 2003;Guenther et al, 2005;Allen et al, 2005;Konarski et al, 2005;Schmahmann & Caplan, 2006;Gianaros et al, 2007;Schweizer et al, 2007). Anatomical studies revealed that via the thalamus, the cerebellum interacts with multiple areas of the prefrontal cortex and subcortex limbic lobe (Middleton & Strick, 2001;Zhu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%